Social Support and its Relationship to the Adaptation of Physical Education Students to the Environment of Yarmouk University - Alzyoud, Khaled Mahmoud (Dirasat: Educational Sciences, 2020)
The study aims to identify the relationship between social support and the adaptation of students of the Faculty of Physical Education at Yarmouk University to the university environment. The study relied on a descriptive-analytical method. A questionnaire was applied to a random sample of (287) male and female students from the Faculty of Physical Education. The results of the study showed that the level of social support among students of the Faculty of Physical Education was high. In addition, the study showed that the level of adaptation of the students of the Faculty of Physical Education to the university environment was at a high level. Moreover, the study revealed that there are statistical differences in the level of social support and in the level of students’ adaptation due to gender and place of residence in favor of males and city, respectively.